The Future of New Learning Way for The Visually Impaired Learners: Use Bionic Eye with Voice Assistant - Che, Kao Sheng (Universitas Negeri Malang, 2021)
Chatbots can be defined as artificial narrow intelligence (ANI) which can perform a single task such as answering people’s question by harnessing the power of machine learning. There is some educational-related chatbots developed to interact with learners in mobile instant messaging (MIM) apps. Nowadays, there are more and more voice assistant developed in our world. They aim to fulfill user requests by choosing the best intent from multiple options generated by its Automated Speech Recognition and Natural Language Understanding sub-systems. Bionic eye is also still develop for the blind, it plays a vital part by restoring the vision. Technologies that are involved in bionic eyes are-multiple unit artificial retina chip system (MARC). This report describes an approach for the design and development of a voice assistant based on chatbot development basis combined with bionic eye application for an eLearning system with the learner’s personal needs.